THE “GRAY ZONES” OF MAPUCHE HISTORIES. INTERNALIZED COLONIALISM, MARGINALITY AND POLITICS OF MEMORY - Nahuelpán Moreno, Héctor (Revista de Historia Social y de las Mentalidades, 2024)
The “gray zones” of Mapuche histories can  be understood as everyday spaces in which  complex social and intersubjectives interactions  develop as part of experiences of social  suffering, ways of survival, resilience, and  resistance performed by Mapuche men and  women under conditions of social marginality  and colonial violence. These spaces, interactions  and experiencies are constitutive of family  histories, of the heterogeneous and contradictory  Mapuche identity, but they are subalternized  within Mapuche official historical, indigenist  and nationalist narratives. This article discusses  the idea of “gray zones” of Mapuche histories  as an interpellation to inter-weave experiencies  and remembrances, in order to deal with the  dispersion and fragmentation of memories that  make possible the reproduction of colonialism  as a mode of hegemony and culture.
Keywords: Mapuche histories; Colonialism; Memories